Downregulation of Smac attenuates H(2)O(2)-induced apoptosis via endoplasmic reticulum stress in human lens epithelial cells - De-qian, Kong (Medicine (Baltimore), 2017)
BACKGROUND: Second mitochondria-derived activator of caspases (Smac) is reported to promote apoptosis. Given the important role of apoptosis in cataract development, the aim of this study was to investigate whether Smac induces human lens epithelial cell (HLEC) apoptosis via endoplasmic reticulum stress (ERS). METHODS: Smac expression was examined by immunohistochemistry in anterior lens capsules from 157 patients with age-related cataracts and 5 normal controls. The role of Smac in hydrogen peroxide (H(2)O(2))-induced ERS and apoptosis was further evaluated using small interfering RNA knockdown in an HLEC line. RESULTS: Notably, Smac expression was significantly higher in patients with cataracts than in controls, but showed no association with cataract severity. Cell survival was inversely correlated with H(2)O(2) concentration, and was most significantly affected at 200 μmol/L. Moreover, flow cytometry revealed that Smac knockdown attenuated H(2)O(2)-induced apoptosis and enhanced apoptotic- and endoplasmic reticulum-related marker expression—including that of glucose-regulated protein 78, C/EBP homologous protein, caspase 3, B-cell chronic lymphocytic leukemia/lymphoma 2-associated X, and BCL2—at the gene and protein level. CONCLUSION: Collectively, these results indicate that Smac plays an important role in ERS-induced apoptosis in HLECs, suggesting its close association with cataract development.